Defect tuned SnO2 nanolayer coated TiO2 1-D core-shell structure for enhanced overall solar water splitting - Thoa Huynh, Thi Kim; Lee, Youngjae; Kalanur, Shankara S.; Seo, Hyungtak (Ceramics International, 2022)
The production of O2 at TiO2 surface during the photoelectrochemical water splitting is the bottleneck of the reaction process indicating the need for surface engineering of TiO2. Here, 1-D TiO2 was coated with the defect tuned SnO2 nanolayer (via sputtering) for enhanced solar water splitting activity. The sputtering strategy allows oxygen vacancy tuning of SnO2 with complete coverage on TiO2. Importantly, the optimized SnO2/TiO2 system exhibited the record photocurrent of 1.85 mA cm−2 at 1.23 V vs. RHE, incident photon to current efficiency of 95% at 350 nm, and H2 and O2 production with ∼90% of faradaic efficiency. Band structure analysis indicated a decrease in work function along with an upward shift of Fermi level and conduction band at the electrolyte interface after SnO2 coating. The present study demonstrates the utilization of oxygen vacancy in SnO2 for the surface engineered electrodes for facile O2 production during solar water splitting.
Keywords: Band structure analysis; Complete coverages; Core shell structure; Faradaic efficiencies; Incident photon-to-current efficiencies; Nano layers; Photoelectrochemical water splitting; Reaction process; Solar water splitting; Surface engineering; Core-shell structure; Oxygen vacancy; Photoelectrochemical water splitting; SnO2; TiO2